Long Time Series in US Fisheries Oceanography - Sam McClatchie; Janet Duffy-Anderson; John C. Field; Ralf Goericke; Dave Griffith; David S. Hanisko; Jonathan A. Hare; Joanne Lyczkowski-Shultz; William T. Peterson; William Watson; Edward D. Weber; Glenn Zapfe (Oceanography, 2014)
Few fisheries oceanography surveys in the United States have sampled hydrography and ichthyoplankton or juvenile fishes for 15 years or more. We describe six long time series surveys, including three from the California Current System, and one each from Alaska (Gulf of Alaska, Bering Sea, and the Arctic), the Northeast US Shelf, and the Gulf of Mexico. We examine the applications of long time series data as well as the output of published analyses, Web-based graphical summaries, and quality controlled data to the broader scientific community (including resource managers and stakeholders). Potential improvements to the surveys using new technologies are evaluated, and possible changes in survey design are discussed. We conclude with a summary of the benefits derived from these long time series fisheries oceanography surveys and make the case for their continuation.